Springs of Variable Stiffness in the Control of Seismic Actions in Buildings (Rudarsko-geološko-naftni zbornik, 2023)
Many regions in the world have experienced the presence of intensive geological events. Given this reality, the control of vibrations caused by earthquakes on buildings is one of the great challenges in seismic regions, as they can cause structural, material, and personal damage, and must be considered with special attention when carrying out a structural project. For this reason, it is necessary to minimize the deleterious effects caused by earthquakes on buildings. In this sense, the present study seeks to evaluate, through the theory of mechanical vibrations, the use of springs of variable stiffness in the control of accelerations induced by seismic action, because springs introduce restoring forces in the system. The evaluation is done through numerical-computational simulation using the finite element method. The frame structure of an idealized building is used in the modelling, where columns and beams are represented by linear elements and the floors by shell elements. In the simulation, springs of variable stiffness are inserted into the joints to control the vibrations produced by earthquakes. These devices are added to the structural system at different heights and directions, aiming to keep the structure's behaviour unchanged, neutralizing the effects of the earthquake. Based on the obtained results, it is possible to verify the required stiffness and the position in which the springs must be inserted to obtain the constancy of the structural frequency of vibration during the earthquake action.